Critical Hole. On a Material Nihilism - Rodríguez, Federico (Escritura e Imagen, 2023)
What are the holes, why do they attract and frighten at the same time, what do they hide? A tentative answer is improvised here from the study of some selected pages of the phenomenological tradition (mainly: Heidegger, Sartre, Granel, and Derrida), showing in what sense the hole is, first of all, the thing itself of criticism (propaedeutics of Kant’s philosophy), that is, the truth of its material reality as an ungraspable perceptual bottom, and, at the same time, the strict genesis of what came to be called in the sixties “deconstruction” (Abbau, Entsetzung).
Keywords: pit; abyss; hell; finitude; gift; transcendental; metaphysics